Meningkatkan Kemampuan Membaca Arab Peserta Didik Madrasah Ibtidaiyah Melalui Pengembangan Media Pembelajaran Monopoli - koderi, koderi; Sari, Titi Puspita (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2021)
This research aims to develop Arabic language learning media with monopoli qira’ah media for learning Arabic reading skills using the development model ADDIE and to find out the feasibility of the media through expert opinion, media expert and materials expert and see student responses to the media developed by researchers. The type of research used in this research is the research method of development R & D (Research and Development). as for the model used is the ADDIE model with 5 stages of research, : (1) analyze, (2) design, (3) development, (4) implementation, (5) evaluation. The data collection instrument was used in the form of a questionnaire given to media expert, materials expert to see the feasibility of the media developed by researchers. The student and teacher response questionnaires are used to see the attractiveness of the media that has been developed. From the results of this research, the researchers produced monopoli qira’ah media by using the ADDIE model. Based on the results of the assessment provided by medis experts get an average score 84,8% with very decent category. As for the results of the research given by material experts, the results obtained an average score of 84% with very decent category.the results of small group trials and large group trials to determine student responses. Small group trial obtained an average score of 84,6% with a very interesting category. While the large group trial obtained an average score 85,7% with a very kinteresting category. And the results of the teacher response get an average score of 92,3% with a very interesting category. Based on the results of research provided by media experts, material experts, student responses and teacher responses, monopoli qira’ah media developed with the ADDIE model for students at MIN at Bandar Lampung is said to be very feasible.